An epithelium is not just an epithelium: Effects of Na, Cl, and pH on olfaction and/or copper-induced olfactory deficits. (February 2019) - Lari, Ebrahim; Razmara, Parastoo; Bogart, Sarah J.; Azizishirazi, Ali; Pyle, Greg G.
Abstract: While the toxic effects of several substances on fish olfaction are well known, studies on how water chemistry affects contaminant-induced olfactory toxicity are rare. In the present study, the effect of water pH or Na concentration on fish olfactory response and Cu-induced olfactory toxicity was investigated. Also, the effects of two sodium salts, NaCl and NaNO3, on olfaction were studied. Juvenile rainbow trout were exposed to 6 and 32 μg/L Cu, each under five different conditions (pH 9, pH 6.5, 20 or 40 mg/L sodium added, or culture water), for 10 days before characterizing fish olfactory response using electro-olfactography (EOG). The results demonstrated that reducing the pH to 6.5 or adding 20 or 40 mg/L Na impairs the fish response to a standard olfactory cue. None of the water treatments were protective against, or synergic with, the toxic effect of Cu on the olfactory system. Of the two Na salts, NaCl caused significantly higher impairment than NaNO3 . The results of the present study demonstrate that water quality modifies contaminant-induced olfactory toxicity, but differently than what is known for other tissues (i.e. gill). Graphical abstract: Highlights: Copper impairs fish olfaction at an environmentally relevant concentration. Increased pH and Na concentration do not protect against toxicity of Cu on olfaction. Addition of Na and Cl and reduction of pH impair fish olfaction.